New Social Mobility Second Generation Pioneers in Europe - Schneider, Jens; Crul, Maurice; Pott, Andreas (IMISCOE Research Series,, 2022)
This open access book comparatively analyses intergenerational social mobility in immigrant families in Europe. It is based on qualitative in-depth research into several hundred biographies and professional trajectories of young people with an immigrant working-class background, but raised in Europe who made it into high-prestige professions. These biographies were collected and analysed by a consortium of researchers in nine European countries from Norway to Spain. Through these analyses, the book explores the possibilities of cross-country comparisons of how trajectories are related to different institutional arrangements at the national and local level. The analysis uncovers the interaction effects between structural/institutional settings and specific individual factors and family backgrounds, and how these successful individuals responsed to and navigated through sector-specific pathways into high-skilled professions, such as becoming a lawyer or a teacher. By this, it also explains why these trajectories of professional success and upward mobility have been so exceptional in the second generation of working-class origins, and it tells us a lot also about exclusion mechanisms that marked the school and professional careers of children of immigrants who went to school in the 1970s to 2000s in Europe - and still do.